The ecological baseline of select endorheic ephemeral pans in an arid African savanna - Wallington, Caroline Ann (My University, 2018)
The mosaic of nutrient-rich hot spots in nutrient-poor savannas is of importance to the functioning of these ecosystems. In the Lephalale plains there are the many ephemeral pan wetlands that have received limited scientific attention and are now under threat from mining in the area. The aim of this study was to gain some insight into the ecological baseline of these systems to possibly inform future studies and management approaches. Pans near the small town of Steenbokpan, Limpopo Province, South Africa were sampled in the summer rainfall season along a transect including three ‘hydro-ecological’ zones being the wetland centre (A), the pan ‘riparian-like’ area (B) and the surrounding representative terrestrial savanna habitat (C). The data gathered included vegetation species composition, tree density, physiochemical characteristics of the top (0- 30cm) and subsoils (30-60 cm) and pan water quality. The non-wetland areas were characterised mostly by forbs such as Limeum and Indigofera species and some hardy grasses including Tragus and Aristida species where more palatable grasses such as Panicum and Digitaria were present only under trees and shrubs. The pans (Zone A) were characterised by wetland grasses, Leptochloa fusca and Echinochloa colona, and had no woody species. Tree density around the pans (Zone B) was greater than the surrounding savanna vegetation (Zone C) and this habitat was characterised by a dominance in fine-leafed Acacia species. This was in contrast to the terrestrial areas that were largely dominated by broad leafed tree and shrub species (Combretum and Grewia sp.). The change from a broad-leaf to fine-leaf dominated habitat is generally associated with a change from nutrient-poor to nutrient-rich soils, which was confirmed in this study. All soil nutrients including key elements and base cations increased significantly from the broadleafed, through fine-leafed savanna and into the wetland soils. The nutrients showed a positive relationship with clay content, increasing from an average of 13% in the dry soils to 34% in the wetland soils. The water holding capacity too was significantly correlated with clay content, thus supporting the hydrological study gradient along which sampling was carried out. Water chemistry results showed the pans to be largely fresh with some high metal concentrations. Overall, the results show that these pans are much higher in soil nutrients and differ in species composition and structure from the surrounding nutrient-poor savanna. This highlights the very important functional role that these pans play in this arid environment with respect to biodiversity and nutrient dynamics. The nutritious Acacia-dominated (nutrient-rich) patches around the pans, as well as the palatable wetland grasses in the pan, will likely result in these habitats being favourable forage sites for game, especially given that these pans will likely be critical water sources for all fauna in the area. These pans are therefore critical habitats to take into account for management interventions as they will be the first to show sign of degradation. Furthermore, these wetlands and enriched savanna patches likely increase heterogeneity and biodiversity and should be priority monitoring sites for managers and targeted for conservation protection as they play a disproportionately large role in the ecological functioning of this landscape. This research has therefore shown that these pans should be highlighted as important in this ecosystem and further research would be able to enhance the understanding of their importance and sensitivity.
A research report submitted to the Faculty of Science, School of Animal, Plant and Environmental Sciences in partial fulfilment of the requirements for the degree of Master of Science, University of the Witwatersrand. Johannesburg, May 2018.